Creative Marketing Strategies to Drive Business Growth in Startup Incubators - Susiang, Maria Imelda Novita (The Eastasouth Management and Business, 2024)
In order to better understand how innovative marketing techniques, contribute to the expansion of startups in incubators, this study focuses on data-driven methodologies, digital marketing tactics, cooperative projects, and storytelling. Emerging topics were discovered through semi-structured interviews with important stakeholders, such as incubator managers, company founders, and marketing experts. topics were then examined using thematic analysis. The results highlight how crucial cooperative marketing initiatives are for maximizing group networks and resources to increase marketing reach. In today's digital-first world, digital marketing techniques including email marketing, social media marketing, content production, and SEO have become essential for businesses to successfully engage with their target audience. Furthermore, brand narrative and storytelling were emphasized as effective strategies for establishing emotional bonds with clients and setting up new businesses apart from rivals. Furthermore, it was discovered that improving campaign efficacy and refining marketing tactics required the use of data-driven marketing techniques. There is a discussion of how these findings affect startup incubators and suggestions for encouraging successful marketing tactics.